Long Term Effects of Mindfulness on Quality of life in Irritable Bowel Syndrome - Zomorrodi, Saeedeh (Iran J Psychiatry, 2015)
Objectives: This study aimed to investigate the long-term effects of mindfulness-based therapy on improving life quality of patients with irritable bowel syndrome. Method: This was an experimental study including 24 patients (12 from each group) with IBS syndrome were selected based on the ROMEIII criteria and were randomly placed in the test and control groups. In both groups, the scales of the IBS-QOL34 Questionnaire were applied as assessment tool. Experiment group was subjected to the MFT (mindfulness-based therapy), while the control group received no intervention. After the two-month follow up, both groups were once again evaluated through the IBS-QOL34 scales. Results: There is not significant difference between trial and control group in starting of the study in demographic and quality of life status. The findings of covariance analysis revealed that the difference between the experiment and the control groups at follow-up was significant (p = 0.01). The results showed that the MFT has long-term effects on the life quality of patients suffering from IBS. Conclusion: The MFT could be considered as a new, effective and stable method in psychotherapy, particularly in psychosomatic disorders such as Irritable Bowel Syndrome.